PENGARUH KOMPRES HANGAT ZINGIBER OFFICINALE TERHADAP TINGKAT NYERI GOUT ARTHRITIS PADA LANSIA DI PUSKESMAS TALISE - Delvi abas; Siti Yartin; Beny H.L Situmorang (Universitas Pahlawan Tuanku Tambusai, 2026)
ABSTRACT Background: According to World Health Organization data, the prevalence of gout is almost the same in Europe (30%) and North America (27%), while in Southeast Asia and New Zealand, the prevalence of gout is higher. The purpose of this study was to analyze the effect of warm compresses of Zingiber officinale on the level of gout arthritis pain in the elderly at the Talise Community Health Center. Methods: This study was quantitative with an analytical approach using a preexperimental design. The population in this study consisted of elderly patients treated at the Talise Community Health Center from January to March, totaling 82 individuals. The sample consisted of 29 respondents, selected using purposive sampling. Research Results: Based on the Wilcoxon statistical test results, the p-value was 0.000. This indicates that the p-value (probability) is lower than the p-value = 0.05. Conclusion: There is a significant effect of Zingiber Officinale warm compresses on the level of gout arthritis pain in elderly patients at the Talise Community Health Center. Suggestion: Health institutions such as the Talise Community Health Center are expected to consider implementing ginger warm compresses as a complementary nursing procedure in the care of patients with gout arthritis pain. Keywords: gout arthritis, zingiber officinale, compress;